수박 덩굴쪼김병에 대한 간편 저항성 검정법 확립 - 조은주(Eun Ju Jo); 최용호(Yong Ho Choi); 장경수(Kyoung Soo Jang); 김헌(Hun Kim); 최경자(Gyung Ja Choi) (Sigmulbyeong yeon'gu, 2017)
Root-dipping inoculation method has been widely used to determine the resistance of watermelon to Fusarium oxysporum f. sp. niveum causing Fusarium wilt. Although this method leads to the precise results of plant disease responses, more rapid and efficient assay methods have been still required because the root-dipping inoculation method is labor-intensive and time-consuming. In this study, we established a simple and effective bioassay method based on the comparison of various inoculation methods and growth conditions. To develop the system, the occurrence of Fusarium wilt on four resistant and susceptible cultivars was investigated by four different inoculation methods, root-dipping, scalpel, tip and soil-drenching methods. Of these inoculation methods, scalpel method resulted in clear plant disease resistance responses with the simplicity. With the use of scalpel method, we also explored the disease development of the cultivars depending on inoculum concentration, growth stage of seedlings, and incubation temperature after inoculation. Furthermore, we found that the resistance degrees of 23 cultivars derived by scalpel inoculation method were similar to the results by root-dipping method established previously. Fusarium oxysporum f. sp. niveum에 의해 발생하는 수박의 덩굴쪼김병 저항성을 검정하기 위해 뿌리 침지 접종 방법이 많이 사용되어 왔다. 이 방법은 정확한 저항성 검정 결과를 제공하나 많은 노동력과 시간이 소요되어 보다 빠르고 효율적인 검정 방법이 요구되어 왔다. 본 연구에서 수박 덩굴쪼김병의 간편한 대량 저항성 검정법을 확립하기 위해 저항성 및 감수성 4개 품종의 유묘에 F. oxysporum f. sp. niveum을 네 가지 접종 방법(뿌리 침지, scalpel, tip 및 무상처 토양 관주법)으로 접종하고 덩굴쪼김병 발생을 조사하였다. 이들 중 scalpel 접종 방법은 실험 방법이 간단하고 정확한 저항성 반응을 보였다. 우리는 scalpel 접종 방법을 이용하여 수박의 생육 시기, 접종원 농도 및 접종 후 재배 온도 등의 발병 조건에 따른 위의 품종들의 덩굴쪼김병에 대한 저항성 반응을 조사하였다. 그리고 이들 결과로부터 확립한 scalpel 방법의 효용성은 시판 품종 23개의 덩굴쪼김병균에 대한 저항성 정도를 뿌리침지 방법과 비교하여 확인하였다. 이상의 결과를 종합하여 수박 덩굴쪼김병에 대한 간편 대량 저항성 검정 방법으로 수박 종자를 파종하여 온실에서 10-13일 동안 재배한 수박 유묘의 뿌리를 scalpel을 이용하여 상처를 준 후에 $3.0{×}10^6\;conidia/ml$의 포자현탁액을 포트당 10 ml씩 관주하고 $25^{°}C$에서 하루에 12시간씩 광을 조사하면서 약 4주 동안 재배하는 것을 제안하고자 한다.